Can You Escape? The Pharmacology Review Virtual Escape Room. (February 2021) - Smith, Miranda Michelle; Davis, Rebecca G.
Background: Clinical learning activities in apre-licensure nursing program are challenging to rapidly convert to an online format due to their objectives to provide hands-on practice. Previously, students spent their final day ofpharmacology participating in low-fidelity lab-based, simulatedpharmacology activities. Due to a public health crisis, the instructional team had to quickly change course to create an equally engaging virtual activity that provided opportunities forclinical judgment . Aim: In this article, we discuss a virtualpharmacology escape room created using Google forms forpre-licensure nursing students prior to their finalpharmacology course exam. The learning objectives were to review difficult course concepts by making clinical decisions and to practice using medication protocols. Methods: The design and evaluation of a virtualpharmacology escape room are presented to reflect alearner centered approach. Key considerations when designing theescape room were to best use the students' time, to focus on content frequently missed on exams by the student cohort, and to include medication protocols commonly encountered during the clinical part of their program. Results: Surveys provided positive feedback from learners along with suggestions for strengthening futureescape room activities. Most students reported the activity provided opportunities forclinical judgment and was helpful for learning. Conclusion: Benefits of virtualescape rooms are they can be created at no cost to educators of learners and easily accessed using personal electronic devices. Future applications include designing additional escape rooms to aid student learning in challenging nursing coursework, such aspharmacology and clinical courses.